Canadian Clinical Practice Guidelines for Invasive Candidiasis in Adults. Issue 4 (2010) - Bow, Eric J; Evans, Gerald; Fuller, Jeff; Laverdière, Michel; Rotstein, Coleman; Rennie, Robert; Shafran, Stephen D; Sheppard, Don; Carle, Sylvie; Phillips, Peter; Vinh, Donald C
Abstract : Candidemia and invasive candidiasis (C/IC) are life-threatening opportunistic infections that add excess morbidity, mortality and cost to the management of patients with a range of potentially curable underlying conditions. The Association of Medical Microbiology and Infectious Disease Canada developed evidence-based guidelines for the approach to the diagnosis and management of these infections in the ever-increasing population of at-risk adult patients in the health care system. Over the past few years, a new and broader understanding of the epidemiology and pathogenesis of C/IC has emerged and has been coupled with the availability of new antifungal agents and defined strategies for targeting groups at risk including, but not limited to, acute leukemia patients, hematopoietic stem cell transplants and solid organ transplants, and critical care unit patients. Accordingly, these guidelines have focused on patients at risk for C/IC, and on approaches of prevention, early therapy for suspected but unproven infection, and targeted therapy for probable and proven infection.